PSYCHOLOGICAL AND PEDAGOGICAL COMBATING OF BULLYING AMONG PRIMARY SCHOOL STUDENTS - Tretyak, Olga (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article is devoted to the topical problem of psychological and pedagogical counteraction to bullying among primary school students. Based on the analysis of philosophical, psychological and pedagogical literature and taking into account the diversity of the educational process, we have the opportunity to reveal the state of the problem. The purpose of this article is to investigate the role of the educational process in counteracting the occurrence of violence, conflict situations (in particular, bullying).The educational institution plays an important role in creating conditions for students to acquire knowledge in a safe educational environment, developing the attitudes and skills needed to avoid and prevent violence, conflict-free communication, non-violent behavior. Revealing the features of bullying and the specifics of its manifestation in the primary school environment, we focus on the organization of the educational process, which is a means of counteracting, preventing and correcting deviant behavior of participants in the educational process.Teachers have a crucial role in creating a safe educational environment and combating bullying. However, they can cope with this problem only through a systematic approach and support from school management, parents, local government officials and NGOs, as well as the involvement and participation of children and youth.The practical significance of the study is determined by the fact that its results allow to improve the quality of the educational space of the school, increase the effectiveness of its impact on the moral development of the younger generation, to adapt the activities of younger students to real life. In addition, materials of research can be used in the organization of educational work of general education institutions and training of primary school teachers.